Cognitive Profile of Patients with Schizophrenia in North Sumatera Indonesia - Amin, Mustafa M.; Effendy, Elmeida; Loebis, Bahagia (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Cognitive dysfunction is one of the characteristics of schizophrenia traditionally experienced by elderly patients. In the past 25 years, studies have proven that the cognitive dysfunction is an early characteristic of this disease, besides introversion, drug abuse, suicidal behavior, and depressive symptoms. The mini-mental state examination is a test designed to identify functional and organic disorders in psychiatric patients. North Sumatera is often considered as “small Indonesia” due to the variety of tribes live in the province; therefore, a study in relation with the cognitive profile of patients with schizophrenia (PwS) is needed. AIM: We aimed to analyze cognitive function in PwS in the North Sumatera. METHODS: The study was a descriptive study with a cross-sectional approach of cognitive profile of PwS stressing in the age, sex, education, and illness duration of the patients. RESULTS: The results of the study using 200 subjects found that the most affected gender were male (62.5%), between the ages of 25–34 years (46%), with secondary school education background (55.5%), and with an illness duration >1 year (64.0%). The results showed that cognitive function in schizophrenic patients was probable cognitive dysfunction (56.5%). CONCLUSIONS: From the results of this study, it was found that the most affected subjects were men, between 25 and 34 years, with high school education, and the illness lasted more than 1 year. Most of the schizophrenic patients experienced probable cognitive dysfunction.